Adaptabilitas Varietas-varietas Unggul Kacang Tanah pada Tanah Salin - Taufiq, Abdullah; Kristiono, Afandi; Wijanarko, Andy; Rahmianna, Agustina Asri; Iswanto, Rudy; Riyanto, Salam Agus (Jurnal Penelitian Pertanian Tanaman Pangan, 2020)
East Java Province supplies one third of the national peanut production. The farmland of peanut production centers in the region is a coastal area prone to salinity. The use of variety adaptive to salinity stress is an effective strategy to cope sainity problem and to optimize the use of salt-affected land. The aim of the research was to evaluate the adaptability of peanut varieties to salinity stress.The research was conducted in the 2018 dry season in the saline paddy field in Gesikharjo Village, Palang Sub District, Tuban Regency with EC 14.54 dS/m. The treatments consisted of seven groundnut varieties (Singa, Singa, Kancil, Takar 2, Bison, Hypoma 2, Tuban, and Jerapah), using a randomized complete design, four replications. Observations consisted of growth parameters, yield and yield components, proline and macro nutrient (N, P, K) content. The results showed that high salinity stress reduced seed germination, plant growth, yield components and yields of all varieties tested. Based on the ability to survive and yield, Singa variety have showing higher tolerance to salinity stress or more adaptive than other varieties, while the lowest one was found in Jerapah variety. The salinity tolerance of Singa variety did not indicate to be associated with high proline content, but it seem more related to the ability to absorb higher N, and keep K high to reduce negative effect of Na.